Measurement of an excess of B[bar] → D(*)τ-ν[bar]τ decays and implications for charged Higgs bosons - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
Based on the full BABAR data sample, we report improved measurements of the ratios R(D)=B(¯¯¯B→Dτ−¯ντ)/B(¯¯¯B→Dℓ−¯νℓ) and R(D∗)=B(¯¯¯B→D∗τ−¯ντ)/B(¯¯¯B→D∗ℓ−¯νℓ), where ℓ refers to either an electron or muon. These ratios are sensitive to new physics contributions in the form of a charged Higgs boson. We measure R(D)=0.440±0.058±0.042 and R(D∗)=0.332±0.024±0.018, which exceed the standard model expectations by 2.0σ and 2.7σ, respectively. Taken together, the results disagree with these expectations at the 3.4σ level. This excess cannot be explained by a charged Higgs boson in the type II two-Higgs-doublet model. Kinematic distributions presented here exclude large portions of the more general type III two-Higgs-doublet model, but there are solutions within this model compatible with the results.